Heterologous ChAdOx1 nCoV-19 and mRNA-1273 Vaccination - Normark, Johan; Vikström, Linnea; Gwon, Yong-Dae; Persson, Ida-Lisa; Edin, Alicia; Björsell, Tove; Dernstedt, Andy; Christ, Wanda; Tevell, Staffan; Evander, Magnus; Klingström, Jonas; Ahlm, Clas; et al. (The New England journal of medicine, 2021)
Health care workers who had received a dose of ChAdOx1 nCoV-19 were offered a choice of receiving either ChAdOx1 nCoV-19 or mRNA-1273 9 to 12 weeks after the initial dose. Levels of S-specific and RBD-specific IgG increased by a factor of 5 after a ChAdOx1 nCoV-19 boost and by a factor of 115 to 125 after an mRNA-1273 boost.